Alternative Methods of Stress Management in Mariama Bâ’s So Long a Letter - Ndiyah, Florence Y. (International Journal of Language and Literary Studies, 2026)
In So Long a Letter Ramatoulaye’s ordeal, and to a lesser extent Aissatou’s, are indisputable and the subject of numerous studies. These childhood friends grow up to become pioneer professionals in post-independent Senegal. They marry two friends who also form part of the new elite, but they are both betrayed when their husbands, encouraged by Islam and culture, become polygamists. Aissatou divorces and relocates abroad. Ramatoulaye yields to societal pressure and stays married but is abandoned with her twelve children. Modou’s sudden death, the funeral proceedings, the threat of bankruptcy and pressure to quickly remarry further harm Ramatoulaye’s mental health. Confined to her house in the mourning period prescribed by Islam, Ramatoulaye is bent on avoiding Jacqeline’s lot, that of a friend who suffered a nervous breakdown and challenged the diagnosis of depression until modern and traditional medicine failed to cure her. Some studies have highlighted religion, ecotherapy, and sisterhood among the coping strategies employed by Ramatoulaye, but none has analysed these alongside others under the Generalized Resistance Resources (GRRs) coined from the health promotion theory of salutogenesis. Some GRRs perceived as having contributed to Ramatoulaye’s mental restoration include educational empowerment, economic independence, sisterly bonding, introspection and writing.